Produção e caracterização de nanoestruturas de carbono por PECVD - Almeida, Larissa Solano de (2021)
In recent decades, studies and discoveries related to carbon nanostructures have been intensified, mentioning carbon nanotubes, graphene and their derivatives. These structures have unique physical and chemical properties, attributed to their structures, and can be applied in different areas. In the area of biomedicine, carbon nanostructures are highlighted for their biocompatibility with the human body. Amorphous carbon films have great potential to be applied in implant coating, as graphene and its derivatives also have such potential. However, conventional synthesis methods require high temperature, reaching 1000° C. Thus, the plasma-assisted chemical vapor deposition (PECVD) method has been explored to synthesize carbon nanostructures, due to relatively large-scale production and at low treatment temperature. The objective of this work is the production and characterization of carbon nanostructures by the PECVD technique with a DC-pulsed source, using substrates of copper, nickel, titanium and stainless steel 304. The growth of carbon nanostructures was carried out through the use of CH4 precursors and H2 using oxide films of substrates as catalyst, studying the influence of stress on the formation of the catalyst and the influence of the addition of argon and total gas flow on the growth of carbon nanostructures. The techniques for the characterization of the formed nanostructures were X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and electrochemical measurements. The results obtained proved to be promising for the production of carbon nanostructures by PECVD, which technique favored the growth of graphene, carbon nanotube and DLC films on oxidized substrates as a function of treatment parameters at temperatures below the conventional one. Argon was shown to be necessary to obtain crystalline structures, such as graphene and carbon nanotubes. The graphene produced had 2 to 5 layers and the carbon nanotubes have multiple walls. The materials obtained presented good quality and could be used in several areas. Thus, the PECVD technique using pulsed DC source was effective in obtaining characteristic structures of graphene, carbon nanotube and amorphous carbon at low temperature, obtained according to the treatment parameters.